Formulation and Antioxidant Activity of Syrup Preparation Containing Saga Leaf Extract (Abrus precatorius L.) - Dewi, Bheta Sari; Utami, Sheila Meitania; Sayyidah, Sayyidah; Alamsyah, Salwa Season; Rahmadani, Novita Tri (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Saga leaf (Abrus precatorius L.) have tannins, saponins, alkaloids, and flavonoids that have functions as antioxidants. The plant belongs to the Fabaceae family and is widespread in the tropics and subtropics. Syrup is one form of pharmaceutical preparation used in providing drugs in liquid form so that it is easily drunk by patients, especially children. The purpose of this study was to obtain the best syrup preparation formulation physically and its antioxidant activity. Saga leaf are extracted in ethanol and then syrup preparations by adding saga leaf extract with concentration variations of 0.5% (FI), 1% (FII), and 2% (FIII). Evaluation of syrup preparations includes organoleptic, pH, homogeneity, and antioxidant activity test using DPPH (1,1-diphenyl-2-picrylhydrazyl) measured by UV-Vis spectrophotometer at wavelength 516 nm. The results showed that Formula III had the best results, namely clear dark brown organoleptic, slightly viscous shape, distinctive smell and slightly bitter taste, pH 6.15, homogeneous, and the preparation was stable in storage for 12 days and showed the best IC50 value of 116.94 g/mL compared to FI (132.65 g/mL) and FII (118.03 g/mL). The antioxidant activity of saga leaf extract is categorized as moderate. In conclusion, saga leaf can be formulated as a syrup preparation with an extract concentration of 2% in formula III showing effectiveness as the best IC50 value of 116.94 g/mL and the best formulation.